Oil price volatility and industrial productivity: a comparative analysis of Nigeria and Egypt - Ayodele Folasade (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2022)
This study examines the relationship between oil price volatility and industrial productivity in Nigeria and Egypt from 1980 - 2020. The study employs cointegration analysis and the Error Correction model to analyze data. The result shows that oil price volatility hinders industrial productivity in both Countries. But the magnitude of the effect was more in Nigeria than in Egypt. It can be traced to the fact that Nigeria is an importing Country while Egypt is a net exporting country. Also, Nigeria has neglected important sectors like the Industrial sector at the advent of oil, which made Nigeria a mono-product country for decades. Based on these findings, the study recommended diversification of the export revenue base for Nigeria to minimize reliance on oil. Also, alternative energy sources such as biofuel and solar power plants should be developed for the two countries to reduce dependency on oil consumption.